К вопросу анализа и синтеза элементов биомеханических систем - Ткачук, Николай Анатольевич; Веретельник, Юрий Викторович (НТУ "ХПИ", 2004)
The development of methods for the volumetric modelling of endoprosthetic operations on the locomo-torium and spine, postoperative complications is proposed, for determination of prosthetic elements strength and rigidity and for choosing of optimum operative scheme and prosthetic parameters taking into account postoperative complications.
Keywords: опорно-двигательный аппарат; параметры протезов; компьютерное моделирование; индивидуализированное моделирование; костно-металлические блоки; эндопротезирование